Developing a Connected Mathematics Project-Based Mathematics Textbook to Improve Elementary School Students' Conceptual Understanding and Self-Confidence - Azizah Yusra Amaliyah; Syahrina Anisa Pulungan; Filzah Syaurah Dhabitah (Journal of Practice Learning and Educational Development, 2025)
This study aims to develop a mathematics textbook based on the Connected Mathematics Project (CMP) to improve elementary school students' conceptual understanding and self-confidence. The research method used is Research and Development (R&D) with the Plomp development model which includes five stages, namely preliminary investigation, design, realization, trial, and implementation. The research subjects were fifth-grade students of PAB 27 Medan Private Elementary School with instruments in the form of validation sheets, conceptual understanding tests, and self-confidence questionnaires. The results of expert validation showed that the textbook obtained an average score of 77.2% with a very feasible category. The effectiveness test showed an increase in conceptual understanding from 54.3% to 74.6% and self-confidence from 52.1% to 72.8%. This increase places the product in the effective category although it has not yet reached a very effective level. The practicality test conducted through teacher and student responses resulted in an average of 77.5% with a very practical category. Overall, this study concludes that the developed CMP-based textbook is not only substantively feasible but also quite effective in improving students' conceptual understanding and self-confidence, and is practical for use in learning. This product can be used as an alternative, innovative learning resource for elementary school mathematics, with recommendations for further development to enhance interactivity and visualization